Intranasal delivery of Natesto® testosterone gel and its effects on doping markers. Issue 11 (4th November 2016) - Miller, Geoffrey D.; Nair, Vinod; Morrison, M. Scott; Summers, Maggie; Willick, Stuart E.; Eichner, Daniel
Abstract : The laboratory profile of intranasal testosterone gel has not been previously reported from an anti‐doping perspective. Because intranasal testosterone gel is newly available as a commercial product, we sought to examine the laboratory parameters following administration of this formulation, with particular attention to anti‐doping guidelines. Five healthy and active male subjects were administered testosterone intranasal gel three times daily for four weeks, using a pattern of five consecutive days on, two days off. Urine was collected after each five‐day round of drug administration and analyzed using a full steroid screen and isotope ratio mass spectrometry (IRMS). Windows of detection for elevated testosterone/epitestosterone (T/E) and other steroid ratios, World Anti‐Doping Agency (WADA) athlete biological passport (ABP) findings, and IRMS results were analyzed in this study. In the 0–24 h window post‐administration, 70% of samples were flagged with a suspicious steroid profile and 85% were flagged as atypical passport findings according to the WADA ABP steroid module. In the 24–48 h window, 0% of samples displayed suspicious steroid profiles while 40% resulted in atypical passport findings. IRMS testing confirmed the presence of exogenous testosterone in 90% and 40% of samples in the 0–24 h and 24–48 h windows post‐administration, respectively. Additionally, IRMS data were analyzed to determine commonalities in the population changes in δ 13 C values of testosterone, androsterone, etiocholanolone, 5αAdiol, and 5βAdiol. Though no discernible metabolic trend of the route of administration was identified, we discovered that intranasal gel testosterone is detectable using conventional anti‐doping tests. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : A newly commercially available formulation of testosterone, an intranasal gel, was self‐administered by five subjects. The effects of the administration on conventional doping markers are described herein.